2017
DOI: 10.5539/ibr.v10n3p148
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs, Strategy, Venturing Process and Industry Environment: A Configurational Approach to New Venture Emergence

Abstract: This study applied qualitative comparative analysis (QCA) as a viable method for new venture emergence. Through the inclusion of four-dimension variables from individuals, founding strategy, startup process, and environment, the study illuminates the importance of factor independence, factor interdependence, and factor complex causality in understanding new venture emergence. This study demonstrates the benefits of QCA approach to entrepreneurship research, a complement to the conventional variance-based appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…e statistical tool used for the analysis has been R, with the use of the QCA package that applies the advanced Quine-McCluskey algorithm [230]. Although the origins of the QCA method is not a new one [231,232], only recently the research has shown an increasing interest in its use [233][234][235][236] especially for the evaluation of particular qualitative elements in a company or to understand better the necessary conditions to achieve specific business objectives [231,[237][238][239][240][241][242][243][244][245].…”
Section: Methodsmentioning
confidence: 99%
“…e statistical tool used for the analysis has been R, with the use of the QCA package that applies the advanced Quine-McCluskey algorithm [230]. Although the origins of the QCA method is not a new one [231,232], only recently the research has shown an increasing interest in its use [233][234][235][236] especially for the evaluation of particular qualitative elements in a company or to understand better the necessary conditions to achieve specific business objectives [231,[237][238][239][240][241][242][243][244][245].…”
Section: Methodsmentioning
confidence: 99%
“…The study identified various necessity-driven entrepreneurship (NDE) and opportunity-driven entrepreneurship (ODE) and proposed a role model for policymakers to secure a high proportion of ODE in a particular economy. Finally, Ye (2017) applied QCA as a viable method for new venture emergence, stating that a simple contingency approach is not sufficient in entrepreneurship research, as venture creation faces multiple contingencies such as the entrepreneur, the opportunity, the context, the process and the outcome, with significant inter-dependence among these contingencies. The study contributed to both theory building and methodology by applying the QCA method to the TPB in the context of entrepreneurship, considering the configurational view that goes beyond the conventional correlational view.…”
Section: Qualitative Comparative Approach In Entrepreneurship Researchmentioning
confidence: 99%
“…Entrepreneurial process duration can vary among individuals because of their characteristics and context (Ye, 2017) as individuals with greater general and specific human capital are relatively better placed to benefit from both opportunity discovery and opportunity creation (Ucbasaran, Westhead and Wright, 2008). In process-based studies, the focus on human capital contribution has largely remained limited due to concentrating on start-up activities (milestones) rather than entrepreneurial process outcomes (McMullen and Dimov, 2013) that include ventures being created or process exited.…”
Section: Human Capital and Entrepreneurial Processmentioning
confidence: 99%